Does Stimulating Physical Activity Affect School Performance? - Bart H.H. Golsteyn; Maria W. J. Jansen; Dave H. H. Van Kann; Annelore Verhagen (Institute of Labor Economics (IZA), 2019)
This paper investigates whether encouraging children to become more physically active in their everyday life affects their primary school performance. We use data from a field quasi-experiment called the Active Living Program, which aimed to increase active modes of transportation to school and active play among 8- to 12-year-olds living in low socioeconomic status (SES) areas in the Netherlands. Difference-in-differences estimations reveal that while the interventions increase time spent on physical activity during school hours, they negatively affect school performance, especially among the worst-performing students. Further analyses reveal that increased restlessness during instruction time is a potential mechanism for this negative effect. Our results suggest that the commonly found positive effects of exercising or participating in sports on educational outcomes may not be generalizable to physical activity in everyday life. Policymakers and educators who seek to increase physical activity in everyday life need to weigh the health and well-being benefits against the probability of increasing inequality in school performance.
Keywords: I12; C93; I20; 330; education; field quasi-experiment; health behavior; physical activity